The Importance of the Novelty Factor in Teaching Listening Comprehension - Ficzere, Anikó; Haringa, Ivan; Weiss, Ervín (Journal of Education Culture and Society, 2024)
Aim. Acquiring the skill of listening comprehension can be considered as a difficult process, which is influenced by the personality traits of the student. Tolerance of novelty is an inherent and innovative factor in teaching a foreign language, which plays an important role in the effective processing of new information. The aim of the research is to determine the difference in listening comprehension performance between groups with different levels of tolerance of novelty. Methods. We used standardised test to determine listening comprehension efficiency and the subscale of the Tolerance of Ambiguity Scale instrument to determine the degree of tolerance of novelty. The research was implemented with 154 university students who studied professional English at language level B2. Results. A statistically significant difference in listening comprehension between respondents with high and average levels of tolerance of novelty was confirmed. Furthermore, we found significantly different listening performance between respondents with high and low tolerance of novelty. Respondents with a high tolerance of novelty deliver greater results in listening in a foreign language than people with an average and low level of tolerance of novelty. Conclusion. Research shows that students with a higher tolerance of novelty are more willing to experiment with new, alternative forms and language structures in a foreign language. The personality factor of tolerance of novelty belongs to relatively dynamic personality characteristics that can be optimised with the help of the teacher’s deliberate action and in this way simultaneously stimulate the cognitive processes of listening and understanding.